The role of cell death pathways in respiratory viral infection and vaccination: two sides of the same coin - Lee, Sun Min; Kim, Eui Ho (Frontiers in Immunology, 2025)
Cell death pathways play contrasting roles in physiological processes such as responses to viral infections and vaccinations, potentially exerting either detrimental or beneficial effects. On one hand, uncontrolled cell death accompanied by the release of damage-associated molecular patterns (DAMPs) can lead to excessive inflammation and tissue damage. On the other hand, when properly regulated, these processes help establish an immunocompetent environment by activating innate immunity, which in turn stimulate antiviral immune responses. These mechanisms have emerged as promising targets for the development of effective antiviral therapeutics, immunotherapies, and vaccines. Recent advances have elucidated key aspects of cell death and DAMP pathways, highlighting their association with upstream viral sensors, their capacity to regulate immune responses, and their potential as therapeutic targets in the context of respiratory viral infections such as influenza virus and SARS-CoV-2. In this review, we discuss the advantages and disadvantages of cell death and DAMP pathways, focusing on their roles in antiviral immunity and pathogenesis of respiratory viral infections, and vaccine immunogenicity.